Timely initiation of breastfeeding and associated factors among mothers who have infants less than six months of age in Gunchire Town, Southern Ethiopia 2019 - Yohannes, Ephrem; Tesfaye, Tsegaye (Clinical Journal of Obstetrics and Gynecology, 2020)
Background: Timely starting of breastfeeding is defined as the starting of breastfeeding within one hour after childbirth. Globally mothers who practiced breastfeeding within one hour were less than half in percent. In least developed countries like Eastern and Southern Africa including Ethiopia infant breastfeeding practice within one hour were low. The aim of this study was to assess timely initiation of breastfeeding and associated factors among mothers who have an infant less than six months of age in Gunchire town, Southern Ethiopia. Methods: The study was conducted from May 1 to 28, 2019 in Gunchire town. Data were collected by using a structured face to face interview questionnaire. The community based cross-sectional study was employed on 333 women. The study participants were selected by Simple random sampling techniques. The data were coded, entered, cleaned and analyzed by SPSS with windows version 21.0. Binary and multivariable logistic regression statistical model was used. Adjusted odds ratio with 95% CI was computed to see the strength of association. Results: In this study the magnitude of timely initiation of breastfeeding was 80.5%. Governmental employed mothers (AOR=2.914, 95% CI: 1.139, 7.46), Antenatal care follow up (AOR=5.99, 95% CI: 1.29, 27.81), Baby skin to skin contact (AOR=2.4, 95% CI: 1.092, 5.34), Vaginal delivery (AOR=5.82 95% CI: 1.68, 20.14) Institutional delivery (AOR=5.5, 95 CI%: 1.66, 18.3), Good knowledge of breastfeeding (AOR=4.02, 95% CI: 1.04, 15.59) and Breast disease (AOR=0.24, 95% CI: 0.08, 0.73) were significantly associated with timely starting of breastfeeding. Conclusion: More than two third of the mothers timely initiated breastfeeding within one hour after birth. Being governmentally employed, having Antenatal care follows up, skin to skin contact, mode of delivery, knowledge of mothers about breastfeeding and place of delivery were positively and significantly associated with timely initiation of breast feeding, whereas, breast disease was protective against timely starting of breastfeeding. Therefore, we would like to recommend Enamore woreda health office and Gunchire primary Hospital staffs work at MCH clinic to provide appropriate services and stimulate the mothers to initiate breastfeeding, skin to skin contact enhancing within the first hour of birth.